2012
DOI: 10.1210/en.2011-2032
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Distribution, Regulated Expression, and Functional Role of the Anorexigenic Peptide, NUCB2/Nesfatin-1, in the Testis

Abstract: Nesfatin-1, product of the precursor NEFA/nucleobindin2 (NUCB2), was initially identified as anorectic hypothalamic neuropeptide, acting in a leptin-independent manner. In addition to its central role in the control of energy homeostasis, evidence has mounted recently that nesfatin-1 is also produced in peripheral metabolic tissues, such as pancreas, adipose, and gut. Moreover, nesfatin-1 has been shown to participate in the control of body functions gated by whole-body energy homeostasis, including puberty on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 41 publications
2
66
0
2
Order By: Relevance
“…The anatomical location of neurons expressing nesfatin-1 and its coexistence with neurotransmitters suggests that the physiological role of nesfatin-1 is not limited to the regulation of food intake, but also includes the regulation of neuroendocrine and autonomic control of internal organs and emotional reactions (14,22,34). The expression of NUCB2/nesfatin-1 mRNA was also observed in peripheral tissues, including the stomach, duodenum, pancreas, heart, adipose tissue, and testis (19,23,44,48,65). Gastric NUCB2/ nesfatin-1 mRNA expression levels were higher than expression levels in other peripheral organs and brain (48).…”
Section: Artykuł Przeglądowy Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The anatomical location of neurons expressing nesfatin-1 and its coexistence with neurotransmitters suggests that the physiological role of nesfatin-1 is not limited to the regulation of food intake, but also includes the regulation of neuroendocrine and autonomic control of internal organs and emotional reactions (14,22,34). The expression of NUCB2/nesfatin-1 mRNA was also observed in peripheral tissues, including the stomach, duodenum, pancreas, heart, adipose tissue, and testis (19,23,44,48,65). Gastric NUCB2/ nesfatin-1 mRNA expression levels were higher than expression levels in other peripheral organs and brain (48).…”
Section: Artykuł Przeglądowy Reviewmentioning
confidence: 99%
“…This peptide influences water intake (64), energy expenditure (56), sleep (54), blood pressure (61,63), and reproduction (18,19). Serum nesfatin-1 levels correlated positively with increasing BMI, demonstrating that systemic nesfatin-1 levels may be influenced by the body fat (1,44).…”
Section: Artykuł Przeglądowy Reviewmentioning
confidence: 99%
“…Ongoing pre-clinical data suggest the possible use of subcutaneous and intranasal routes of nesfatin-1 administration (Shimizu et al, 2009c), which needs to be further explored. Another important aspect to be unraveled is the weight loss upon chronic administration of nesfatin-1 (Li et al, 2010;Gonzalez et al, 2012;Li et al, 2013;Dong et al, 2013) and possible related changes in energy balance and/or basal metabolic rate (Foo et al, 2008;García-Galiano et al, 2010;Gonzales et al, 2011;Pałasz et al, 2012;Kerbel and Unniappan, 2012;García-Galiano et al, 2012;Ghanbari Niaki et al, 2013;Vas et al, 2013) for which studies so far are limited. In fact, nesfatin-1 has a remarkably prolonged effect on food intake and body temperature (Könczöl et al, 2012).…”
Section: Nesfatin-1 and Anti-obesitymentioning
confidence: 99%
“…Nesfatin-1 injected intracerebroventricularly significantly decreased gastric emptying (García-Galiano et al, 2012). Goebel-Stengel and Wang (2012) showed that NUCB2/ nesfatin-1 immunoreactivity is distributed in mouse brain areas involved in the regulation of stress response and visceral functions activated by an acute psychological stressor suggesting that nesfatin-1 might play a role in the efferent component of the stress response.…”
Section: Introductionmentioning
confidence: 98%
“…García-Galiano et al [29] documented the expression of NUCB2 mRNA in rat, mouse, and human testes, where the NUCB2/Nesfatin-1 protein was found in interstitial mature Leydig cells. Although NUCB2 mRNA levels did not overtly change in the rat testis during pubertal maturation and after short-term fasting, NUCB2/Nesfatin-1 content significantly increased (~10-fold increase) along the puberty-to-adult transition and was markedly suppressed (~4-fold decrease) after fasting.…”
Section: Other Tissuesmentioning
confidence: 99%